Technology use in secondary level of English language teaching: A Literature Review - Luthfiyyah, Roghibatul; Hafifah, Gusti Nur; Ivone, Francisca Maria; Tresnadewi, Sintha (Universitas Muhammadiyah Sidoarjo, 2021)
Technology has been widely used in the education field, especially for teaching language. Many teachers and students believe in the advantages of technology to enhance language learning. There have been many studies investigating the use of technology in secondary language classrooms. Some studies approve that technology can be applied to increase students' language competence. This paper comprehensively analysed the use of technology for English language teaching in the secondary level based on empirical studies. It reviews 57 articles from reputable journals and publishers. The existing literature shows that studying and reviewing the use of technology in ELT leads to a deeper understanding of its potential benefits. Many technology tools have been utilized to support the teaching of English skills. Kinds of learning activities that require technological tools and applications, such as presentation, discussion, assessment are also discussed. Additionally, problems and solutions encountered in the implementation of technology in secondary ELT levels are scrutinized in this study. HIGHLIGTS: Scholars need to set the content and pedagogy first before the technology to obtain meaningful and contextual experiments and discussion in academic circumstances. The finding unveils a fact that technology use in the ELT context contributes more to students' learning strategies, such as learning motivation, engagement, collaborative work, rather than the improvement of students' learning outcomes. This finding can be a rationale to rectify the common logical fallacy encountered among studies that claimed that technology can improve particular language skill.